2020
DOI: 10.3390/rs12091417
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Meteorological and Agricultural Drought in Chitral Kabul River Basin Using Multiple Drought Indices

Abstract: Drought is a complex and poorly understood natural hazard in complex terrain and plains lie in foothills of Hindukush-Himalaya-Karakoram region of Central and South Asia. Few research studied climate change scenarios in the transboundary Chitral Kabul River Basin (CKRB) despite its vulnerability to global warming and importance as a region inhabited with more than 10 million people where no treaty on use of water exists between Afghanistan and Pakistan. This study examines the meteorological and agricultural d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 39 publications
3
9
0
Order By: Relevance
“…The highest drought severity in the Skardu district (−6.06) was observed in the year of 1982 (Figure 5) with an intensity of −1.2 (Figure 6) with a dry spell of 5 months (Figure 4). The results of this study are in line with those of previous studies [45,70,71].…”
Section: Mann-kendall and Spearman's Rho Trend Test Of Spisupporting
confidence: 93%
See 2 more Smart Citations
“…The highest drought severity in the Skardu district (−6.06) was observed in the year of 1982 (Figure 5) with an intensity of −1.2 (Figure 6) with a dry spell of 5 months (Figure 4). The results of this study are in line with those of previous studies [45,70,71].…”
Section: Mann-kendall and Spearman's Rho Trend Test Of Spisupporting
confidence: 93%
“…However, Ahmed et al (2017) [44] and Ullah et al (2018) [88] observed significant drought conditions in the mountainous region of Pakistan due to rainfall variability. Meteorological and agricultural drought conditions were also observed in the period of 2000-2018 for the Chitral Kabul River Basin [45]. It was observed by various researchers that the northern mountainous region of Pakistan was affected by moderate drought conditions during period of 1951-2010 [73,88,89].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Progressive reduction of rainfall could have accelerated the other droughts between 2004 and 2011. This is in agreement with previous studies in Afghanistan [ 36 , 37 , 50 , 51 ]. The southern parts of the country have been strongly affected by climatic changes, especially in winter; and the northwest and the southwest of the country have been more affected by droughts due to alternations in rainfall and temperature [ 38 ].…”
Section: Discussionsupporting
confidence: 94%
“…Most areas were affected by moderate and mild droughts. These results were in line with the other research made for the Kabul river basin [64], in which it was stated that 2000 and 2004 were the years with the worst meteorological drought conditions from the period from 2000 to 2018 and that the trend of meteorological drought changes in KRB was downward. During the studied period most of the northwest, southwest and some eastern areas of the eastern basins in Afghanistan had been influenced by drought.…”
Section: Discussionsupporting
confidence: 92%